High specific surface area N-doped activated carbon from hydrothermal carbonization of shaddock peel for the removal of norfloxacin from aqueous solution. (12th May 2022) - Niu, Xinyong; Liu, Chenglin; Li, Lin; Han, Xiuli; Chang, Chun; Li, Pan; Chen, Junying
Abstract: A novel N-doped activated carbon (NAC) derived from shaddock peel was investigated to remove norfloxacin (NFX) from aqueous solution. The Box-Behnken central composite design (BBD) was used to optimize the preparation conditions of NAC. The specific surface area of NAC was 2, 481.81 m 2 g −1, which was obtained at 1, 106 K activation temperature, 2.4 h residence time, and 2.3:1 mass ratio of KOH to hydrochar. Moreover, the equilibrium data were perfectly represented by Langmuir and Koble-Corrigan isotherms, and the adsorption process was precisely described by the pseudo-second-order kinetic model. Besides, the adsorption of NFX on NAC was mainly controlled by π-π electron-donor-acceptor (EDA) interaction, hydrophobic effect, hydrogen-bonding, electrostatic interaction and Lewis acid-base effect. The maximum monolayer adsorption capacity of NFX was 746.29 mg g −1 at 298 K, implying that NAC was a promising adsorbent for the removal of NFX from aqueous solution. HIGHLIGHTS: The specific surface area of N-doped activated carbon prepared by hydrothermal carbonization and KOH activation is as high as 2481.81 m 2 g −1 . The maximum monolayer adsorption capacity of norfloxacin on NAC-1106 was 746.29 mg g −1 at 298 K. The adsorption mechanism of NFX on NAC was investigated by XPS, Raman, FTIR and so on. Graphical Abstract